Assessment of copper-iron catalyst supported on activated carbon for low-temperature nitric oxide reduction by hydrogen - Ibrahim, Yakub; Mohamad Hardyman, Barawi; McGregor, James (IOP Publishing Ltd, 2021)
It is pertinent to assess the performance of a sustainable system that can treat nitrogen oxides (NOx) emissions from combusting biomass waste. Low-temperature selective catalytic reduction is attractive due to the longer catalyst lifetime and the possibility to use carbon-based catalysts. Hence, this study explores this system with the utilization of: (i) a cost-effective catalyst support, i.e. activated carbon derived from abundant biomass waste; (ii) a renewable reductant, i.e. hydrogen; and (iii) Earth-abundant metal catalysts, i.e. copper and iron. The catalyst was prepared by impregnating metal oxides (Cu and Fe) over palm kernel shell activated carbon (PKS). The catalyst was characterised by hydrogen-temperature programmed reduction (H2-TPR) and nitric oxide-temperature programmed desorption (NO-TPD). H2-TPR revealed an increase in the reducibility, attributed to the synergistic effects between Cu and Fe. However, these catalyst sites favour nitrous oxide (N2O) formation as shown via NO-TPD. Meanwhile, the catalyst activity has also been investigated in a fixed-bed reactor. It showed that the 100% conversion can be achieved at 200°C, but the selectivity towards nitrogen formation is as low as 40%. Therefore, investigating the optimum design of PKSCuFe catalyst is justifiable to improve the performance of low-temperature selective catalytic reduction.